Teacher Basic Skills in Learning Science in Junior High Schools Facing the 21st Century - Muhlis H. Usman; Agil Al Idrus; Aris Doyan; Harry Soeprianto; Aliefman Hakim (Postgraduate, University of Mataram, 2021)
This study aims to determine the level of teacher skills in science learning in junior high schools facing the 21st century, especially the basic teaching skills of teachers. The research examined consisted of two types of data, namely qualitative and quantitative from the eight basic skills of teachers. The qualitative and quantitative data were interpreted and obtained information from the group discussion forums. The results show that the level of basic teaching skills for science teachers in Mataram City Junior High School is 33.4% very good, 60% in a good position, 6.6% at a sufficient level. Meanwhile, of the eight basic teaching skills of science teachers, the skills to open lessons and various teaching skills for junior high school science teachers in Mataram have very good skills, while explaining skills are still lacking, and basic teaching skills in very good categories are found in junior high school science teachers who are senior or already occupying a position. Coach level IV/a and above.